2013
DOI: 10.4276/030802213x13679275042681
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Client-Centredness in Student Occupational Therapists

Abstract: Introduction: While the occupational therapy profession emphasizes the importance of a client-centred approach, the student perspective on development of client-centredness has been absent in the research literature. The purpose of this grounded theory study was to gain an understanding of occupational therapy students' perceptions of the curricular and practice experiences that contributed to their client-centred development. Method: Study participants were recruited from three cohorts (n = 29) of an entry-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…For example, they initially struggled to identify occupations not stated in participant goals and instead viewed these occupations as interfering with planned intervention. As is supported in the literature, students came to understand what client-centered practice looks and feels like as they learned to understand the difference between their values and those of their participants, choosing to meet their participant's current needs instead of sticking to their original therapy plan (Maloney & Griffith, 2013;Ripat, Wener & Dobinson, 2013). Actual "doing" seemed to help students appreciate the intervention plan as a flexible tool rather than a template.…”
Section: Discussionmentioning
confidence: 95%
“…For example, they initially struggled to identify occupations not stated in participant goals and instead viewed these occupations as interfering with planned intervention. As is supported in the literature, students came to understand what client-centered practice looks and feels like as they learned to understand the difference between their values and those of their participants, choosing to meet their participant's current needs instead of sticking to their original therapy plan (Maloney & Griffith, 2013;Ripat, Wener & Dobinson, 2013). Actual "doing" seemed to help students appreciate the intervention plan as a flexible tool rather than a template.…”
Section: Discussionmentioning
confidence: 95%
“…Categories were grouped into six overarching themes; subsequently, relationships between themes were explored. A framework was developed to support the findings based on analysis of the data and further review of the literature [30]. Trustworthiness was addressed through triangulation of investigators and sources, member-checking to ensure participant ideas were not misconstrued, and an audit trail recording development of the data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, further analysis of the theme internalizing client-centredness, from the original study, was completed by the first two authors (PW & JR). Internalizing client-centredness referred to the "ways in which students and graduates felt they 'became' client-centred in their thinking, attitudes and behaviours, and began to identify themselves as client-centred practitioners" [30]. The authors sought to explicate this theme in order to better understand the processes involved and implications for interprofessional education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors concluded that the students developed empathy consistent with the principles of client-centred practice. In a recent study, Ripat, Wener, and Dobinson (2013) explored how student occupational therapists develop client-centredness—or the attitude or belief in being client-centred—throughout their educational program and into their first years of practice. These authors discuss several themes important to the client-centred development of students, such as internalizing client-centredness, relationship building, the academic/practice discrepancy, and the subsequent difficulty students experience in bridging this gap (Ripat et al, 2013).…”
mentioning
confidence: 99%